Regional Food Supply System Planning: A System Dynamics Analysis of Broiler Chicken Supply and Price Stabilization Policies in Indonesia - Avif Haryana; Suprayogi Suprayogi; Rachmawati Wangsaputra; Rajesri Govindaraju (Journal of Regional and City Planning, 2026)
Price instability in Indonesia’s broiler sector is not only an industry-level supply chain problem but also a food supply planning issue with regional relevance, as broiler meat is an important source of affordable animal protein. Despite repeated government interventions, including reference prices, final stock day-old chicks (FS DOC) supply regulation, hatching egg culling, and early culling of breeder hens, live bird prices frequently have remained below production cost. This study developed an explanatory system dynamics model to examine how recurrent live bird price instability emerges endogenously from the structure of the broiler food supply system. The model integrates downstream broiler meat demand, slaughterhouse activity, live bird market dynamics, integrator and non-integrator grow-out production, FS DOC allocation, cold storage, the grandparent stock (GPS) and parent stock (PS) breeding subsystem, and grandparent stock day-old chicks (GPS DOC) import determination. The main novelty lies in a dual-control structure that combines long-term capacity correction through demand-driven GPS DOC import adjustment and short-term operational control through hatchery setting adjustment. Baseline simulation broadly and qualitatively reproduced the recurrent pattern of live bird price fluctuations and prolonged periods of price pressure relative to production cost. Scenario analysis indicated that hatchery setting adjustment is the strongest short-run leverage point, because it moderates excess FS DOC realization before surplus propagates downstream to live bird and broiler meat markets. Demand-driven GPS DOC import adjustment has limited short-run influence because of long biological delays but remains important for aligning long-term breeding capacity with downstream requirements. Within the modeled system, cold storage operates as a residual downstream buffer rather than the primary source of stabilization. Overall, the findings suggest that broiler price stabilization should be treated as a multi-horizon food supply planning problem that requires coordinated control of upstream breeding capacity, hatchery operations, market absorption, and downstream buffering.